Analisa Potensi Wisata Kuliner Khas Betawi Dalam Pengembangan Pariwisata Di Kota DKI Jakarta - Yudhiet Fajar Dewantara (Politeknik Sahid, 2021)
There are very few conventional culinary tours (Betawi culinary specialties) in DKI Jakarta due to the displacement of the Betawi people to the suburbs, as a result there are many native foods that are almost extinct in the capital city of Jakarta. . The purpose of the research is to identify potential places for Betawi culinary tourism, to recognize Betawi specialties, to recognize the position of culinary tourism in tourism development. The research method used for this research is an associative qualitative method in which the problem formulation helps researchers to construct a relationship between the social situation or domain of one area and another. Using observation data collection techniques, interviews, documentation, and triangulation / combination. The results of the study indicate that the potential for typical Betawi culinary tourism is spread throughout DKI Jakarta, starting from the area, Setu babakan, Rawa belong, Meruya, Condet and Pasar Minggu. There is Betawi culinary originating from side dishes of betawi, typical Betawi spinggan food, insedential Betawi food, typical Betawi snacks. And by typical Betawi, each place has its own power over the existing food. The conclusion of this research is that tourists need food to eat, and this can have a positive impact on tourism development. The role of tourists for culinary tours must be better in processing everything both products and servants. Not only that, the Regional Government also provided training called the Professional Training Center which was shown for actors involved in tourism. And the government recommends that besides holding training, apart from providing a special place for Betawi culinary tourism, there is promotional assistance carried out by the government so that people who sell Betawi specialties are helped.